Rancang Bangun Web Service Api Dan Dokumentasi Rest Api Web Portal Unit Kegiatan Mahasiswa Di Politeknik Negeri Lampung - Leo, Leo Pradana; Ambarwari, Agus; Putra, Septafansyah Dwi (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2023)
Currently, the student activity unit of the Lampung State Polytechnic itself already has a website that is connected to the official website of the Lampung State Polytechnic. Based on the results of research on 8 student activity units in Polinela, the web is considered to still not meet the needs of each student activity unit of the State Polytechnic in Lampung. then it is necessary to develop a backend system based on the Application Programming Interface (API) that can be implemented to create an Application and Mobile-based web. So an API-based system can be produced with a Representational State Transfer (REST) architecture and web REST API documentation portal for student activity units of the State Polytechnic in Lampung to make it easier for frontend developers to create a web